Additive Manufacturing of Intertwined Electrode Pairs ‐ Guided Mass Transport with Gyroids. Issue 1 (4th January 2023) - Wiesner, Florian; Limper, Alexander; Marth, Cedric; Brodersen, Anselm; Wessling, Matthias; Linkhorst, John
Abstract : Intertwined electrode pairs, manufactured by selective laser melting, provide high surface‐to‐volume ratios and a constant interelectrode distance, which results in a homogeneous electric field. Gyroid convective channels are integrated into the structure to further enhance convective transport. Further details can be found in the article number 2200986 by John Linkhorst and co‐workers.